Digital Capitalism and Social Inequality: A Critical Analysis - Pariyar, Anita Kumari (NPRC Journal of Multidisciplinary Research, 2026)
Introduction: Digital capitalism has emerged as a dominant mode of economic organization in the twenty-first century, transforming production, labor, governance, and everyday social relations through data extraction, platformization, and algorithmic control. Although digital technologies are often celebrated for promoting innovation, efficiency, and inclusion, growing scholarly debates suggest that digital capitalism also reproduces and intensifies existing forms of social inequality. Previous studies have largely focused on either technological advancement or economic transformation, with limited emphasis on the interconnected structural, political, and social dimensions of inequality within digital capitalism. Methods: This paper adopted a conceptual and critical research design based exclusively on secondary data. A comprehensive review of peer-reviewed books, journal articles, policy reports, and scholarly publications was conducted using perspectives from critical political economy, sociology of technology, neoliberalism, and theories of power and inequality. Results: The study demonstrates that digital capitalism generates and sustains inequality through platform monopolies, surveillance practices, precarious digital labor, unequal digital infrastructures, and algorithmic forms of control. These mechanisms disproportionately disadvantage marginalized populations along lines of class, gender, geography, and the Global North–South divide. The analysis further reveals that states and global regulatory institutions often facilitate digital accumulation by weakening labor protections and limiting democratic accountability. At the same time, technological change operates within broader structures of neoliberal globalization and capitalist power relations rather than as a socially neutral process. Conclusion: Digital capitalism reflects the complex interaction between technological innovation, economic accumulation, and structural inequality. Addressing the widening socio-economic disparities of the digital age requires democratic governance of digital infrastructures, stronger regulatory frameworks, protection of labor rights, and alternative models of inclusive digital development. Originality: This study contributes to existing scholarship by integrating political, economic, technological, and sociological perspectives into a single analytical framework to examine how digital capitalism reproduces inequality. Unlike many studies that focus narrowly on technological innovation or economic growth, this research provides a comprehensive critical analysis of the structural mechanisms and power relations shaping inequality in the digital era.